PENERAPAN MODEL DISCOVERY LEARNING UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA PESERTA DIDIK KELAS VII.2 SMPN 4 MANDAU - Warisma, Lini; Zulkarnain, Zulkarnain; Yuanita, Putri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This study aims to improve the learning process and improve mathematics learning outcomes by applying the discovery learning model. This type of research is a classroom action research conducted in two cycles, each of which consists of planning, implementing, observing, and reflecting. The subjects of this study were students of class VII 2 SMPN 4 Mandau in the odd semester of the 2019/2020 school year which consisted of 18 male students and 14 female students. The data collection instruments in this study were the observation sheet and the mathematics learning result test sheet. The observation sheet was analyzed qualitatively, while the mathematics learning outcome test was analyzed quantitatively by descriptive statistics. The results of this study indicate that the quality of each encounter with the discovery learning model is getting better for each cycle and the percentage of the frequency of students who reach the KKM in the knowledge aspect at the basic score, PH I, and PH II respectively 37.5%, 12.5%, and 21. , 88%, as well as the percentage of the frequency of students who reached the KKM in the skills aspect of PH I and PH II, 28.13% and 56.25%, respectively. Thus the results of this study indicate that the application of the discovery learning model can improve the learning process and does not improve the mathematics learning outcomes of class VII.2 students of SMPN 4 Mandau in the odd semester of the 2019/2020 academic year on the subject matter of the set.Key Words: Mathematics Achievement, Discovery Learning Model, Class Action Research